La desinformación en redes sociales y sus repercusiones frente a la pandemia por covid 19 en la Parroquia San Carlos cantón Quevedo, año 2021 - Alava Carriel, Ariel Josue (2021)
The research that has been carried out is with the purpose of knowing how the phenomenon of misinformation has impacted during the covid pandemic19; within a sector of the San Carlos parish of the Quevedo canton. Taking into account that during the current pandemic the use of social networks has increased, a place where news that does not always adhere to reality commonly circulates, this topic has been selected, since it is recognized as an element of importance for properly deal with the pandemic. For the purposes of this study, different research methods, techniques and instruments have been used, which have helped to collect enough information to analyze the problem addressed here; For this, a group of 80 people who live in the San Ramón neighborhood was selected, and through a survey it was determined that people have a frequent activity in the use of social networks, and that there is also the need to educate the population, so that when they are informed, they do so in a more objective and safe way. What was deduced at the end of the study, is that without a doubt, the misinformation in this sector of the parish; it has influenced people's emotions, even conditioning them to adopt erratic behavior or opinion.